Pengaruh Konsentrasi Gula Dan Waktu Fermentasi Terhadap Yield Asam Asetat Menggunakan Bahan Baku Nira Nipah Dan Bakteri Acetobacter Aceti - Futhanul Wewe; Chairul Chairul; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Nipah plants (Nypa fruticans) grown in province of Riau especially in Lubuk Muda vilage, Bengkalis regency with land area about 50 hectares. Nipah produce sap with high sugar concentration which can be used as an alternative material for acetic acid production by fermentation using microorganisms. The purpose of this study was to determine the effect of the initial sugar concentration of nipah sap and the time of acetic acid fermentation on yield of acetic acid using Saccharomyces cerevicae and Acetobacter aceti microorganisms. Variation of initial sugar concentration was 10%, 20% and 30%, while the fermentation time is 1, 3, 5, 7 and 9 days. Acetic acid fermentation process was carried out at pH 6, stirring speed of 200 rpm and 10% inoculum. The results of analysis using the Nelson-Somogyi method revealed that the highest sugar concentration was evaporation of nipa sap 30% (172.7223 g/L). The highest concentration of acetic acid was obtained 59.399 g/L or 5.94% and yield was 51.599%. The concentration and the highest yield was obtained at 30% evaporation and the 9th day of acetic acid fermentation.Keywords : Acetic acid, Acetobacter aceti, fermentation, inoculum, nipah sap